Relationship Between Response Time Level Of Patient Handling With Patient Satisfaction Level In Emergency Of Klakah Lumajang Community Health Center - Tomo, Tomo; Ro'isah, Ro'isah; Abidin, Zainal (NHM PRESS, 2024)
The health center is one of the health facilities that are widely used by the community where the health center and its network are the spearhead of health services in Indonesia. Response time is an indicator of speed and accuracy in handling patients which is calculated from the time the patient arrives until the patient is treated. The purpose of this study was to determine the Relationship between the Level of Response Time Speed of Patient Handling and the Level of Patient Satisfaction in the Emergency Room of the Klakah Health Center. In this study, the sample determination used the Accidental Sampling method and a Cross-sectional research design with data collection techniques using questionnaires and observations. The population in this study was 100 emergency room patients who met the inclusion and exclusion criteria, with a sample of 80 respondents.The results obtained that the Level of Response Time Speed of Handling Patients in the Emergency Room of Klakah Health Center, Lumajang Most of them are in the fast category, namely 67 people (83,8%), in the slow category there are 12 respondents, namely (15%) and in the very slow category there is 1 respondent, namely (1.3%). This finding indicates that response time greatly influences the level of patient satisfaction at the Klakah Health Center Emergency Department in the fast category, namely 67 people (83.8%).